A multi-dimensional metric for facilitating sustainable food choices in campus cafeterias. (1st November 2016) - Chen, David M.; Tucker, Bronwen; Badami, Madhav G.; Ramankutty, Navin; Rhemtulla, Jeanine M.
Abstract: Demand-side initiatives to alter food choices have been repeatedly identified as important tools in reducing the environmental and resource use impacts of our global food systems, and effective strategies to identify and motivate key dietary changes are needed. The environmental and resource use impacts of the most common meals served in the undergraduate residence cafeterias at McGill University in Montreal are evaluated and presented, to inform sustainable food choices in an easy to use manner. The life-cycle land and water use, and greenhouse gas emissions for the 19 most-used ingredients are calculated and compared for different iterations of two typical meals using these ingredients, accounting for multiple origins, methods of production of ingredients, and meal types. These three metrics are kept distinct to better communicate trade-offs and inform decision-making. Overall, meals containing beef and cheese have 2–12 times higher associated water, land use and greenhouse gas emissions impacts than meals with other protein sources and drive impacts more than provenance or production methods assessed. The impacts of eggs and chicken are comparable to or lower than those of many plant-based ingredients. This suggests that the adoption of a lacto-vegetarian diet has an unclear environmental benefit; eating chicken instead of cheese would be more beneficial in some cases. For some ingredients, impacts vary greatly depending on their provenance, independent of transport. There are also substantial trade-offs between the metrics for greenhouse vegetables, but these trade-offs are minimized in milder climates. Given this high context dependence, greater transparency is needed in supply chains at the consumer level, to improve the reliability of food sustainability metrics. Highlights: The environmental impacts of common meals in a university cafeteria are assessed. Chicken and eggs have impacts similar to those of many plant-based foods. Meals with cheese and beef have larger impacts than meals with other protein sources. Vegetarian diets that replace cheese for meat may not be environmentally beneficial. Greenhouse vegetables have low land/water use but high GHG emissions in cold climates.